MANAJEMEN KEUANGAN PENDIDIKAN ISLAM: PRINSIP, IMPLEMENTASI, DAN TANTANGAN TATA KELOLA - Urip Widiyanto (Ulul Amri: Jurnal Manajemen Pendidikan Islam, 2025)
Financial management is a strategic aspect of governance in Islamic educational institutions, as it is directly related to operational sustainability, the quality of educational services, and public accountability. This article aims to analyze the concepts, principles, and implementation of financial management in Islamic education by highlighting practices of budget planning, execution, and supervision, as well as comparing them with financial management in non-Islamic educational institutions. This study employs a qualitative–descriptive approach based on a literature review, strengthened by empirical examples from Pondok Tahfidz Al-Fatah Kuripan Lor Pekalongan. The findings indicate that financial management in Islamic education requires a dual approach, namely compliance with state regulations and alignment with Sharia principles. The main challenges include limited administrative capacity, suboptimal digitalization, and potential conflicts of interest in oversight mechanisms. This article emphasizes the importance of strengthening hybrid accounting systems, transparency, and participatory supervision to enhance public trust and ensure the sustainability of Islamic educational institutions.